2021
DOI: 10.3390/ijerph18084163
|View full text |Cite
|
Sign up to set email alerts
|

What Do the Managers Think of Us? The Older-Worker-Perspective of Managers’ Attitudes

Abstract: Background: Due to demographic changes, the need to prolong working life has become increasingly salient. Paradoxically, stereotyping and discrimination against workers based on their age can limit possibilities for a long working life. A large body of research has investigated attitudes towards older workers; however, less is known about differences across occupational groups as well gender differences. Aim: To compare perceptions of the managers’ perceptions of older workers between employees from mainly sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Managers are less subjected to more soft influences, such as organisational factors, in their evaluations of employees. This might be linked to the literature on age stereotypes and the idea that managers provide an evaluation based on an image of older workers where the health impairments (as assessed by work ability) have a strong influence [ 4 , 41 , 42 , 43 , 44 ]. Previous research has found that while managers’ attitudes toward soft skills (reliability and loyalty) have improved over time, their attitudes toward hard skills (such as physical stamina) have not improved [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Managers are less subjected to more soft influences, such as organisational factors, in their evaluations of employees. This might be linked to the literature on age stereotypes and the idea that managers provide an evaluation based on an image of older workers where the health impairments (as assessed by work ability) have a strong influence [ 4 , 41 , 42 , 43 , 44 ]. Previous research has found that while managers’ attitudes toward soft skills (reliability and loyalty) have improved over time, their attitudes toward hard skills (such as physical stamina) have not improved [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, managers and employers are generally found to hold more positive than negative attitudes towards older workers (Jenkins and Poulston 2014 ; Jensen and Møberg 2012 ; Kluge and Krings 2008 ; Meng et al 2021 ; Van Dalen et al 2009 ). The positive stereotypes and beliefs include that older workers are committed, loyal, honest, trustworthy, more stable, dependable, and less likely to miss work or turnover quickly (Posthuma and Campion 2007 ).…”
Section: Introductionmentioning
confidence: 99%